Curing catalyst for use in curing polymers and method for producing same, moisture-curable composition, and method for producing cured product
The use of a titanium compound and organic onium salt complex as a curing catalyst addresses the toxicity and stability issues in existing silicone-based rubber compositions, achieving rapid and consistent curing with improved safety and environmental performance.
Patent Information
- Application Number
- JP2022540289
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-30
- Filing Date
- 2021-07-26
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-07-26
AI Technical Summary
Existing curing catalysts for silicone-based rubber compositions, such as tin carboxylate compounds and titanate ester compounds, face issues with toxicity, environmental concerns, and variable curing rates affected by humidity, leading to instability in the cured product.
A curing catalyst complex comprising a titanium compound and an organic onium salt, specifically a quaternary phosphonium salt, is used to enhance the curing rate and safety of the polymerization process, avoiding the use of toxic tin compounds.
The proposed catalyst system achieves a significant increase in curing rate while ensuring high safety and environmental sustainability, with improved stability and consistency of the cured product across different humidity levels.
Smart Images

Figure 0007659329000001 
Figure 0007659329000002 
Figure 0007659329000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curing catalyst used for curing a polymer and a method for producing the same, a moisture-curable composition, and a method for producing a cured product. [Background technology]
[0002] One-component moisture-curing rubber compositions generally have a fast curing rate and are easier to work with than two-component compositions because they do not require weighing and mixing various additives such as base polymers, crosslinking agents, and catalysts before use.
[0003] Known examples of these one-liquid moisture-curable rubber compositions include silicone rubbers, modified silicone rubbers, urethane rubbers, and polysulfide rubbers. Organopolysiloxane compositions are widely used as one-liquid moisture-curing rubber compositions for silicone rubber, and they cure at room temperature to produce rubber elastomers. Polymeric siloxane compounds with -Si-O- bonds formed by cross-linking organosiloxane as the main chain are widely used in the fields of construction, civil engineering, electrical and electronics, and automotive industries, because of their excellent properties such as water repellency, heat resistance, weather resistance, cold resistance, and electrical insulation.
[0004] One-liquid moisture-curable rubber compositions of modified silicone rubber include compositions containing a polymer having a crosslinkable reactive hydrolyzable silicon functional group with a polyether backbone. This polymer curable composition has better storage stability, weather resistance, foaming resistance and discoloration resistance than polyurethane rubber, and has better curing properties than polysulfide rubber, is less polluting to the environment and is non-toxic.
[0005] The reaction mechanism in the process in which the silicone rubber and modified silicone rubber become a cured product is said to be due to a condensation reaction or addition reaction of reactive hydrolyzable silicon-containing groups in the presence of water, and it is believed that polymerization proceeds to form a polymer cured product with a three-dimensional network structure. In order to rapidly proceed with curing in this reaction, a curing catalyst is used (Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-41358 [Patent Document 2] Japanese Patent Application Laid-Open No. 60-161457 [Patent Document 3] Special Publication No. 63-42942 [Patent Document 4] JP 2003-147220 A [Patent Document 5] Patent No. 5446265 Summary of the Invention [Problem to be solved by the invention]
[0007] Tin carboxylate compounds, alkyl tin salt compounds, and the like have traditionally been used as curing catalysts for curing compositions of silicone rubbers and modified silicone rubbers having this reactive hydrolyzable silicon-containing group. However, due to concerns that they may have an effect on living organisms as endocrine disruptors, a combined catalyst of carboxylic acid and amine has been proposed as a moisture-curing composition that does not use these substances (Patent Document 1). However, there is a problem in that a sufficient curing speed cannot be obtained during application.
[0008] Patent Documents 2 and 3 propose using titanate compounds such as diisopropoxytitanium bis(alkylacetoacetonate) as catalysts, but these compounds are susceptible to decomposition by moisture contained in additives or fillers in the composition, and the curing speed varies depending on the humidity during application, making it difficult to obtain a stable cured product.
[0009] Patent Document 4 proposes using a titanium tetracarboxylate compound as a catalyst, but there is a problem in that the curing speed is not satisfactory for practical use. Patent Document 5 proposes using a quaternary ammonium salt as a catalyst, but this has the problem that a sufficient curing speed cannot be obtained during application. Therefore, there has been a demand for the development of a curing catalyst that is highly safe (low toxicity and low environmental pollution) and has a practical curing speed.
[0010] In view of the above-mentioned conventional techniques, an object of the present invention is to provide a curing catalyst which is highly safe and has a practical curing rate. [Means for solving the problem]
[0011] According to the present invention, there is provided a curing catalyst [B] for use in curing a polymer [A] having a reactive hydrolyzable silicon-containing group, comprising: The curing catalyst [B] contains a complex of a titanium compound [B1] and an organic onium salt [B2], The titanium compound [B1] is provided as a curing catalyst [B] represented by chemical formula (1). (R 1 -O) n Ti-A 4-n (1) (R in the formula 1 is a substituted or unsubstituted hydrocarbon group, n is 1 to 4, and A is a β-diketone group.
[0012] The inventors of the present invention have conducted extensive research and found that the curing rate of the polymer [A] is significantly increased when a curing catalyst [B] containing a complex of a titanium compound [B1] and an organic onium salt [B2] is used, leading to the completion of the present invention. This catalyst does not contain tin, so it is highly safe. In addition, it can be produced at low cost. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below.
[0014] The curing catalyst [B] of the present invention is used for curing a polymer [A] having a reactive hydrolyzable silicon-containing group. The polymer [A] is preferably a polymer that is liquid at room temperature.
[0015] 1. Polymer [A] The polymer [A] has at least one reactive hydrolyzable silicon-containing group at the molecular end or side chain per molecule. The reactive hydrolyzable silicon-containing group may be present at the end of the polymer [A] molecule, or at the side chain, or may be present at both the end and the side chain. The reactive hydrolyzable silicon-containing group may be at least one per molecule of the polymer [A], but from the viewpoint of curing speed and cured physical properties, it is preferable that there are 1.5 or more groups per molecule on average. A known method can be used to bond the reactive hydrolyzable silicon-containing group to the main chain polymer.
[0016] The reactive hydrolyzable silicon-containing group is a group having a silicon atom bonded to a reactive group consisting of a hydrolyzable group (e.g., halogen, alkoxy, alkenyloxy, acyloxy, amino, aminooxy, oxime, amide) or a hydroxyl group, and has the property of undergoing a condensation reaction in the presence of moisture or a crosslinking agent, and if necessary, by using a catalyst, etc. Specific examples include halogenated silyl groups, alkoxysilyl groups, alkenyloxysilyl groups, acyloxysilyl groups, aminosilyl groups, aminooxysilyl groups, oximesilyl groups, and amidosilyl groups.
[0017] Here, the number of reactive hydrolyzable groups bonded to one silicon atom is selected from the range of 1 to 3. The reactive hydrolyzable groups bonded to one silicon atom may be one type or multiple types. Furthermore, a reactive hydrolyzable group and a non-reactive hydrolyzable group may be bonded to one silicon atom, or a hydrolyzable group and a hydroxyl group may be bonded to one silicon atom. As the reactive hydrolyzable silicon-containing group, an alkoxysilyl group (including a monoalkoxysilyl group, a dialkoxysilyl group, and a trialkoxysilyl group) is particularly preferable in terms of ease of handling.
[0018] Among the above alkoxysilyl groups, trialkoxysilyl groups are preferred because they have high activity and provide good curability, and the resulting cured product has excellent recovery, durability, and creep resistance, whereas dialkoxysilyl and monoalkoxysilyl groups are preferred because they have excellent storage stability and provide cured products with high elongation and strength. The combined use of a polymer [A] in which the reactive hydrolyzable silicon-containing group is a dialkoxysilyl group and a polymer [A] in which the reactive hydrolyzable silicon-containing group is a trialkoxysilyl group is preferable because it provides a good balance between the physical properties and curability of the cured product.
[0019] Examples of the polymer [A] include an organic polymer [A1] and an organopolysiloxane [A2].
[0020] (Organic polymer [A1]) The organic polymer [A1] used in the present invention has a main chain containing carbon atoms, such as an alkylene oxide polymer, a polyester polymer, an ether-ester block copolymer, a polymer of an ethylenically unsaturated compound, or a polymer of a diene compound.
[0021] The alkylene oxide polymer may be [CH2CH2O] n [CH(CH3)CH2O] n [CH(C2H5)CH2O] n [CH2CH2CH2CH2O] n Examples include those having one or more of the repeating units such as those mentioned above. Here, n is the same or different and is an integer of 2 or more. These alkylene oxide polymers may be used alone or in combination of two or more. Copolymers containing two or more of the above repeating units may also be used.
[0022] Examples of polyester polymers include those having, as repeating units, carboxylic acids such as acetic acid, propionic acid, maleic acid, phthalic acid, citric acid, pyruvic acid, and lactic acid, their anhydrides, and their intramolecular and / or intermolecular esters and their substitution products.
[0023] Examples of ether-ester block copolymers include those having both the repeating units used in the alkylene oxide polymers described above and the repeating units used in the polyester polymers described above as repeating units.
[0024] Examples of the polymer of the ethylenically unsaturated compound and the diene compound include homopolymers of ethylene, propylene, acrylic acid esters, methacrylic acid esters, vinyl acetate, acrylonitrile, styrene, isobutylene, butadiene, isoprene, chloroprene, etc., or copolymers of two or more of these. More specifically, examples include polybutadiene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, ethylene-butadiene copolymer, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, polyisoprene, styrene-isoprene copolymer, isobutylene-isoprene copolymer, polychloroprene, styrene-chloroprene copolymer, acrylonitrile-chloroprene copolymer, polyisobutylene, polyacrylic acid ester, polymethacrylic acid ester, etc. These may be used alone or in combination of two or more.
[0025] As the organic polymer [A1], an organic polymer having a polar group such as a nitrogen-containing characteristic group in the molecule can also be used. Specific examples of the nitrogen-containing characteristic group include (thio)urethane group-derived linking groups such as (thio)urethane group, allophanate group, other N-substituted urethane group, and N-substituted allophanate group, (thio)urea group, biuret group, other N-substituted urea group, N,N'-substituted urea group, N-substituted biuret group, and other N-substituted urea group-derived linking groups such as N,N'-substituted biuret group, amide group, N-substituted amide group-derived linking groups, and imino group-derived linking groups, (thio)ester group, (thio)ether group, and the like, but are not limited thereto. Among these, nitrogen-containing characteristic groups are preferred from the viewpoint of high curability, and (thio)urethane group-derived linking groups and (thio)urea-derived linking groups are more preferred from the viewpoint of ease of synthesis. The organic polymer [A1] may contain only one nitrogen-containing group, or may contain one or more types of nitrogen-containing groups, where the terms "(thio)" and "N-substituted" are as defined above.
[0026] When the organic polymer [A1] contains a polar group such as the nitrogen-containing characteristic group, the toughness of the cured product is improved, and the curability and adhesive strength are also increased. In particular, when the crosslinkable silicon group is linked to the main chain via a polar group such as a nitrogen-containing characteristic group, the curability is further increased. The reason for this is that the polar groups of the nitrogen-containing characteristic group strongly attract each other due to interactions such as hydrogen bonds. It is believed that the strong attraction between the polar groups of the nitrogen-containing characteristic group causes the molecules of the curable resin to be strongly bonded (domain formation), which results in the toughness of the cured product. In addition, when the crosslinkable silicon group is linked to the main chain via a polar group such as a nitrogen-containing characteristic group, when the nitrogen-containing characteristic groups form a domain, the crosslinkable silicon groups also come close to each other, which increases the contact probability between the crosslinkable silicon groups, and further, it is believed that the condensation reactivity between the crosslinkable silicon groups is improved by catalytic curing by the polar group in the nitrogen-containing characteristic group.
[0027] Such organic polymer [A1] (modified silicone-based polymer) can be produced by known methods such as the method described in Japanese Patent Publication No. 61-18569, or is commercially available. Examples of commercially available products include Kaneka MS Polymer Series (MS Polymer S203, MS Polymer S303, MS Polymer S903, MS Polymer S911, MS Polymer SAX520, etc.), Silyl Series (Silyl Polymer SAT200, Silyl Polymer MA430, Silyl Polymer MAX447, etc.), MA Series, SA Series, and OR Series manufactured by Kaneka Corporation; and ES Series (ES-GX3440ST, etc.), ESGX Series, etc. manufactured by Asahi Glass Co., Ltd.
[0028] The number average molecular weight of the organic polymer [A1] used in the present invention is not particularly limited, but an excessively high molecular weight has a high viscosity and is difficult to use when made into a curable composition, so that the number average molecular weight is preferably 30000 or less. Such an organic polymer can be produced by a known method, but a commercially available product such as Kaneka MS Polymer manufactured by Kaneka Corporation may also be used.
[0029] (Organopolysiloxane [A2]) The organopolysiloxane [A2] used in the present invention is composed of a siloxane bond represented by Si-O as the main chain, and furthermore, an organic group is bonded to the silicon atom that constitutes the siloxane bond.Specific examples of such organic groups include alkyl groups such as methyl, ethyl, propyl, butyl, etc.; cycloalkyl groups such as cyclohexyl, etc.; alkenyl groups such as vinyl, isopropenyl, substituted vinyl, etc.; substituted allyl groups such as allyl, crotyl, methallyl, etc.; aryl groups such as phenyl, toluyl, xylyl, etc.; aralkyl groups such as benzyl, phenylethyl, etc.; and groups in which all or part of the hydrogen atoms of these organic groups are substituted with halogen atoms, such as chloromethyl, 3,3,3-trifluoropropyl, etc.
[0030] As the organopolysiloxane [A2], (-Si(R)2-O-) m (In the formula, R is the same or different and represents an organic group, and m is an integer of 2 or more.) Examples include those having a repeating unit represented by the following formula: (-Si(CH3)2-O-) m (-Si(C2H5)2-O-) m (-Si(Ph)2-O-) m (-Si(-CH=CH2)2-O-) m Examples include those having one or more kinds of repeating units such as the above. Here, m may be the same or different and is an integer of 2 or more. The organopolysiloxane [A2] may be composed of a single main chain, or may be composed of two or more kinds of main chains.
[0031] Even if the organopolysiloxane is linear, it can be trifunctional (R'SiO 1.5 ) or branched including tetrafunctional (SiO2). Depending on the physical properties and applications of the cured product, bifunctional (R'2SiO) or monofunctional (R'3SiO 0.5 ) may be combined (wherein R' is an organic group). Furthermore, the hydrolyzable silicon-containing group may be bonded either to the molecular terminal or in the middle of the molecular chain. Organopolysiloxane generally has the average composition formula R a SiO 4-a / 2 (For example, Japanese Patent Application Laid-Open No. 2005-194399 and Japanese Patent Application Laid-Open No. 8-151521, etc.) The above notation follows this.
[0032] Although there are no particular limitations on the viscosity of the organopolysiloxane [A2] used in the present invention, those with an excessively high viscosity may reduce workability and impair the physical properties of the resulting cured product, so it is desirable for the viscosity to be in the range of 0.025 to 100 Pa·s at 25° C. Such organopolysiloxanes can be produced by known methods, but commercially available products such as the Tosseal series manufactured by GE Toshiba Silicones, Ltd., the Sealant series manufactured by Shin-Etsu Chemical Co., Ltd., and the SH series manufactured by Dow Corning Toray Co., Ltd. can also be used.
[0033] 2.Curing catalyst [B] The curing catalyst [B] contains a complex of a titanium compound [B1] and an onium salt [B2]. This complex is a reaction product that can be obtained by reacting the titanium compound [B1] with the onium salt [B2].
[0034] <Titanium compounds [B1]> The titanium compound [B1] is represented by chemical formula (1). (R 1 -O) n Ti-A 4-n (1) (R in the formula 1 is a substituted or unsubstituted hydrocarbon group, n is 1 to 4, and A is a β-diketone group.
[0035] n may be, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, or may be within a range between any two of the values exemplified herein.
[0036] R 1 The substituted or unsubstituted hydrocarbon group represented by the formula (I) is a substituted or unsubstituted aliphatic or aromatic hydrocarbon group, and an aliphatic hydrocarbon group is preferred.
[0037] Examples of the hydrocarbon group include alkyl groups (e.g., methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, nonyl, and decyl) and oxyalkylene groups.
[0038] R 1 At least one of R is preferably an alkyl group having 8 or more carbon atoms or an oxyalkylene group. 1 At least one of the above is preferably a hydrocarbon group (other hydrocarbon group) that is neither an alkyl group nor an oxyalkylene group having 8 or more carbon atoms. The number of carbon atoms of the other hydrocarbon group is, for example, 1 to 7, and preferably 1 to 5. The number of carbon atoms is specifically, for example, 1, 2, 3, 4, 5, 6, or 7, and may be within a range between any two of the numbers exemplified here. The other hydrocarbon group is preferably an alkyl group, and more preferably a branched alkyl group. The number of the other hydrocarbon group is 0, 1, 2, 3, or 4.
[0039] The number of carbon atoms in an alkyl group having 8 or more carbon atoms is, for example, 8 to 20, and preferably 8 to 15. Specific examples of the number of carbon atoms are 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20, and may be within a range between any two of the numerical values exemplified here.
[0040] The oxyalkylene group is represented by chemical formula (3). The number of atoms in the main chain of the oxyalkylene group is, for example, 4 to 20, and more preferably 6 to 14. Specific examples of the number of atoms are 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20, and may be within a range between any two of the numerical values exemplified here. R 6 -(OR 7 )m- (3) (R in the formula 6 is a substituted or unsubstituted hydrocarbon group having 1 to 10 carbon atoms, R 7 is a substituted or unsubstituted hydrocarbon group having 2 to 10 carbon atoms, and m is an integer of 1 to 10),
[0041] R 6 The number of carbon atoms in R is preferably 1 to 6, more preferably 1 to 4. 7The number of carbon atoms in the alkyl group is preferably 2 to 6, and more preferably 2 to 3; and m is preferably 1 to 6, and more preferably 1 or 2.
[0042] Examples of the oxyalkylene group include groups obtained by removing the terminal hydroxyl groups from the alcohols shown below. Examples of such alcohols include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monopentyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono-t-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-t-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol monopentyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-t-butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, dipropylene glycol monopentyl ether, dipropylene glycol monoisopropyl ether, and dipropylene glycol mono-t-butyl ether. For example, when the alcohol is butyl carbitol (also known as 2-(2-butoxyethoxy)ethanol), the oxyalkylene group is 2-(2-butoxyethoxy)ethyl, and when the alcohol is butyl cellosolve (also known as 2-butoxyethanol), the oxyalkylene group is 2-butoxyethyl.
[0043] Examples of the β-diketone group represented by A include diketones such as 2,4-pentanedione, 2,4-hexanedione, 2,4-pentadecanedione, 2,2,6,6-tetramethyl-3,5-heptanedione, 1-aryl-1,3-butanediones such as 1-phenyl-1,3-butanedione and 1-(4-methoxyphenyl)-1,3-butanedione, 1,3-diphenyl-1,3-propanedione, 1,3-bis(2-pyridyl)-1,3-propanedione and 1,3-bis(4-methoxyphenyl)-1,3-propanedione, and 3-benzyl-2,4-pentanedione, methyl acetoacetate, Examples of the esters include ketoesters such as ethyl acetoacetate, butyl acetoacetate, t-butyl acetoacetate, and ethyl 3-oxohexanoate; ketoamides such as N,N-dimethyl acetoacetamide, N,N-diethyl acetoacetamide, and acetoacetanilide; malonic acid esters such as dimethyl malonate, diethyl malonate, and diphenyl malonate; and malonic acid amides such as N,N,N',N'-tetramethylmalonamide and N,N,N',N'-tetraethylmalonamide. Diketones such as 2,4-pentanedione, 1-aryl-1,3-butanedione, and 1,3-diaryl-1,3-propanedione are particularly preferred.
[0044] Among the titanium compounds represented by chemical formula (1), tetraisopropoxytitanium, triisopropoxyoctoxytitanium, triisopropoxy 2-(2-butoxyethoxy)ethoxytitanium, and triisopropoxy 2-butoxyethoxytitanium are more preferred from the standpoints of catalytic activity, compound stability, and ease of handling. The titanium compounds [B1] may be used alone or in combination of two or more kinds.
[0045] <Organic onium salt [B2]> The organic onium salt [B2] is a salt containing an organic onium. The organic onium may be one in which at least one hydrogen atom of the onium is substituted with a hydrocarbon group, and preferably one in which all hydrogen atoms of the onium are substituted with a hydrocarbon group. An example of the counter anion of the organic onium is hydroxide, but it may be another anion. The organic onium salt [B2] may be a quaternary ammonium salt, a quaternary phosphonium salt, a quaternary imidazolium salt, a quaternary pyrrolidinium salt, a quaternary pyridinium salt, a quaternary piperidinium salt, a quaternary pyrazolium salt, a tertiary sulfonium salt, a tertiary oxonium salt, or the like. The organic onium salt [B2] is preferably an organic onium salt other than a quaternary ammonium hydroxide, and more preferably a quaternary phosphonium salt.
[0046] The organic onium salt [B2] is more preferably a quaternary phosphonium hydroxide represented by the following formula (2).
[0047] [ka] (In the formula, R 2 , R 3 , R 4 , R 5 are the same or different and each represents a substituted or unsubstituted hydrocarbon group. X represents a hydroxyl group.
[0048] R 2 , R 3 , R 4 , R 5The substituted or unsubstituted hydrocarbon group represented by is a substituted or unsubstituted aliphatic or aromatic hydrocarbon group, and an aliphatic hydrocarbon group is preferred. As the aliphatic hydrocarbon group, a straight-chain or branched alkyl group is preferred. The number of carbon atoms in the hydrocarbon group is preferably 1 to 16. Specifically, the number of carbon atoms is, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16, and may be within a range between any two of the numbers exemplified here. As the aliphatic hydrocarbon group, for example, a saturated hydrocarbon group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, a hexyl group, a cyclohexyl group, a heptyl group, or an octyl group, or an unsaturated hydrocarbon group such as a vinyl group, an allyl group, a prenyl group, a crotyl group, or a cyclopentadienyl group, and a methyl group, an ethyl group, a butyl group, an octyl group, a dodecyl group, or a hexadecyl group is preferred.
[0049] Examples of the aromatic hydrocarbon group include a phenyl group, a tolyl group, and a benzyl group.
[0050] Examples of the substituent of the hydrocarbon group include a methoxy group, an ethoxy group, a hydroxy group, an acetoxy group, etc. Examples of the substituted aliphatic or aromatic hydrocarbon group include an alkoxyalkyl group such as a methoxymethyl group, a methoxyethyl group, an ethoxymethyl group, an ethoxyethyl group, etc., a hydroxyalkyl group such as a hydroxymethyl group, a hydroxyethyl group, a 3-hydroxypropyl group, etc., and a 2-acetoxyethyl group.
[0051] Specific examples of the phosphonium hydroxide represented by chemical formula (2) include tetramethylphosphonium hydroxide, tetraethylphosphonium hydroxide, tetrapropylphosphonium hydroxide, tetrabutylphosphonium hydroxide, tetraoctylphosphonium hydroxide, tributyldodecylphosphonium hydroxide, tributylhexadecylphosphonium hydroxide, butyltriphenylphosphonium hydroxide, benzyltriphenylphosphonium hydroxide, and tetraphenylphosphonium hydroxide. In particular, tetrabutylphosphonium hydroxide, tetraoctylphosphonium hydroxide, tributyldodecylphosphonium hydroxide, and tributylhexadecylphosphonium hydroxide are preferred.
[0052] <Reaction of titanium compound [B1] with organic onium salt [B2]> The complex of the titanium compound [B1] and the organic onium salt [B2] is, for example, a transparent liquid, and can be obtained by reacting the mixture of the two at, for example, 40 to 100° C. Specifically, the temperature is, for example, 40, 50, 60, 70, 80, 90, or 100° C., and may be within a range between any two of the numerical values exemplified here. The molar ratio of the titanium compound [B1] to the organic onium salt [B2] in the mixture is, for example, 0.1 to 100, and may be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 50, or 100, and may be within a range between any two of the numerical values exemplified here.
[0053] 3. Moisture-curable composition The moisture-curable composition of the present invention contains the above-mentioned curing catalyst [B] and polymer [A], and may contain other additives described below as necessary. The moisture-curable composition of the present invention can be prepared by mixing the two under dry conditions, and the mixing form is not particularly limited. Usually, mixing is performed under an atmosphere of a temperature of about 15 to 30°C and 60% RH or less.
[0054] In the moisture-curable composition of the present invention, the content of the curing catalyst [B] is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, and particularly preferably 3 to 8 parts by weight, relative to 100 parts by weight of the polymer [A]. If the content of the curing catalyst [B] is less than 0.1 parts by weight, the curing performance is insufficient, and if it exceeds 20 parts by weight, the recovery rate of the cured product after curing, physical properties such as weather resistance, and stability during storage may be deteriorated. The content of the curing catalyst [B] is specifically, for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 parts by weight relative to 100 parts by weight of the polymer [A], and may be within the range between any two of the numerical values exemplified here.
[0055] The moisture-curable composition of the present invention may further contain a filler [C]. Examples of fillers include calcium carbonate, kaolin, talc, fumed silica, precipitated silica, anhydrous silicic acid, hydrous silicic acid, clay, calcined clay, glass, bentonite, organic bentonite, silasburn, glass fiber, asbestos, glass filament, crushed quartz, diatomaceous earth, aluminum silicate, aluminum hydroxide, zinc oxide, magnesium oxide, and titanium dioxide. The filler may be used alone or in combination of two or more. The addition of a filler improves the handling of the moisture-curable composition. It also acts as a rubber reinforcement agent for the cured product. The greatest advantage is that the amount of resin used can be reduced by adding it as an extender, thereby reducing costs.
[0056] Among these, calcium carbonate and titanium oxide are preferred from the viewpoint of maintaining excellent surface non-tackiness, 50% modulus, workability, weather resistance, etc. of the curable composition after curing. When calcium carbonate is used, its proportion is preferably 1 to 200 parts by weight, more preferably 50 to 200 parts by mass, per 100 parts by weight of the polymer [A]. Within the above range, the properties after curing are not impaired.
[0057] The moisture-curable composition of the present invention may further contain additives that are usually added to curable compositions, such as other curing catalysts, curing accelerators, colorants, plasticizers, curing retarders, anti-sagging agents, anti-aging agents, and solvents.
[0058] Other curing catalysts include, for example, metal curing catalysts such as organotin compounds such as dibutyltin dilaurate and dibutyltin bis(acetylacetonate), organoaluminum compounds such as aluminum tris(acetylacetonate) and aluminum tris(ethylacetoacetate), organozirconium compounds such as zirconium tetra(acetylacetonate) and zirconium tetrabutylate, and amine compounds such as 8-diazabicyclo[5,4,0]undecene-7 (DBU), 2-tertiarybutyl-1,1,3,3-tetramethylguanidine-1,5,7-triazabicyclo[4.4.0]-5-decene, ethylenediamine, diethylenetriamine, 3,3-diaminopropylamine, and triethylenetetramine.
[0059] As the curing accelerator, for example, various known amino group-substituted alkoxysilane compounds or their condensates can be used. Specific examples include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(trimethoxysilylpropyl)ethylenediamine, δ-aminobutyl(methyl)diethoxysilane, N,N-bis(trimethoxysilylpropyl)ethylenediamine, and partial hydrolysis thereof, which also have the effect of improving adhesion to the substrate.
[0060] Specifically, the coloring agent may be iron oxide, carbon black, phthalocyanine blue, phthalocyanine green, or the like.
[0061] Specific examples of the plasticizer that can be used include phthalate esters such as dibutyl phthalate, dioctyl phthalate, and butyl benzyl phthalate; fatty acid carboxylate esters such as dioctyl adipate, dioctyl succinate, diisodecyl succinate, and butyl oleate; glycol esters such as pentaerythritol esters; phosphate esters such as trioctyl phosphate and tricresyl phosphate; epoxy plasticizers such as epoxidized soybean oil and epoxy benzyl stearate; and chlorinated paraffin.
[0062] Specific examples of the anti-sagging agent that can be used include hydrogenated castor oil, silicic anhydride, organic bentonite, and colloidal silica.
[0063] Other additives that may be used include adhesion promoters such as phenolic resins and epoxy resins, ultraviolet absorbers, radical chain inhibitors, peroxide decomposers, and various types of antioxidants.
[0064] The curable composition of the present invention is sufficiently stable at room temperature, and therefore has excellent storage properties, and when it comes into contact with moisture, the curing reaction proceeds spontaneously due to the curing catalyst [B] added. In addition, the snap time (the time until the composition becomes semi-gelled and loses fluidity) and tack-free time (the time until the surface tack disappears) are short, and the composition has excellent workability.
[0065] Due to the above-mentioned characteristics, the curable composition of the present invention can be used as a one-component sealant. Specifically, it is suitable for use as a sealant, adhesive, sealant, waterproofing material, etc. for buildings, ships, and vehicles such as automobiles. EXAMPLES
[0066] The present invention will now be described in detail with reference to examples, but the scope of the present invention is not limited thereto.
[0067] <Production Example 1: Tetrabutylphosphonium Salt (Complex 1)> Tetrabutylphosphonium bromide (6.7874 g, 0.02 mol) was dissolved in dehydrated methanol (20 ml) and passed through a column packed with strong basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol). Then, about 35 ml of dehydrated methanol was passed through the column, to obtain 66.0555 g of a methanol solution of tetrabutylphosphonium hydroxide with a hydroxyl conversion rate of 55.3%.
[0068] 55.9491 g of this methanol solution was passed again through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corporation, which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through to obtain 98.3155 g of a tetrabutylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 99.5%.
[0069] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final reduced pressure: 85 mmHg) to give a 17.6% methanol solution (tetrabutylphosphonium hydroxide:methanol=1:40).
[0070] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 15.69 g (0.01 mol) of 17.6% tetrabutylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 14 mmHg) to remove isopropanol and methanol, obtaining 8.39 g of a pale yellow solid tetrabutylphosphonium salt (complex 1). 2.1 g of isopropanol was further added, and the mixture was heated in a 60°C water bath to dissolve, obtaining 10.39 g of a pale yellow liquid.
[0071] <Production Example 2: Tetraethylphosphonium Salt (Complex 2)> Tetraethylphosphonium bromide (4.5434 g, 0.02 mol) was dissolved in 20 ml of dehydrated methanol and passed through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corporation, which had been previously substituted with dehydrated methanol), followed by passing about 35 ml of dehydrated methanol through the column, to obtain 66.7811 g of a tetraethylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 54.9%.
[0072] 56.6752 g of this methanol solution was passed again through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corporation, which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through to obtain 99.0416 g of a tetraethylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 96.7%.
[0073] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final reduced pressure: 85 mmHg) to give an 11.4% methanol solution (tetraethylphosphonium hydroxide:methanol=1:40).
[0074] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 14.41 g (0.01 mol) of 11.4% tetraethylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 7.23 g of tetraethylphosphonium salt (complex 2) as a yellow liquid. 1.82 g of isopropanol was further added, and the mixture was heated in a 60°C water bath to dissolve, obtaining 8.94 g of a yellow liquid.
[0075] <Production Example 3: Tetraoctylphosphonium Salt (Complex 3)> Tetraoctylphosphonium bromide (11.2743 g, 0.02 mol) was dissolved in 20 ml of dehydrated methanol and passed through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), followed by passing about 35 ml of dehydrated methanol through the column, to obtain 62.1133 g of a methanol solution of tetraoctylphosphonium hydroxide with a hydroxy conversion rate of 52.6%.
[0076] 51.9749 g of this methanol solution was passed again through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through, to obtain 87.9017 g of a tetraoctylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 94.9%.
[0077] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final reduced pressure: 85 mmHg) to give a 27.8% methanol solution (tetraoctylphosphonium hydroxide:methanol=1:40).
[0078] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 18.03 g (0.01 mol) of 27.8% tetraoctylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 10.83 g of tetraoctylphosphonium salt (complex 3) as a yellow liquid. 2.71 g of isopropanol was further added, and the mixture was heated in a 60°C water bath to dissolve, obtaining 13.26 g of a yellow liquid.
[0079] <Production Example 4: Tributyldodecylphosphonium Salt (Complex 4)> 9.0353 g (0.02 mol) of tributyldodecylphosphonium bromide was dissolved in 20 ml of dehydrated methanol and passed through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), followed by passing about 35 ml of dehydrated methanol through the column, to obtain 62.3120 g of a methanol solution of tributyldodecylphosphonium hydroxide with a hydroxy conversion rate of 49.5%.
[0080] 52.1445 g of this methanol solution was passed again through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through to obtain 94.7871 g of a tributyldodecylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 98.0%.
[0081] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final reduced pressure: 85 mmHg) to give a 23.2% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:40).
[0082] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 16.79 g (0.01 mol) of 23.2% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 9.64 g of tributyldodecylphosphonium salt (complex 4) as a yellow liquid. 2.43 g of isopropanol was further added, and the mixture was heated and dissolved in a 60°C water bath, obtaining 11.78 g of a yellow liquid.
[0083] <Production Example 5: Tributylhexadecylphosphonium salt (complex 5)> 10.1538 g (0.02 mol) of tributylhexadecylphosphonium bromide was dissolved in 20 ml of dehydrated methanol and passed through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), followed by passing about 35 ml of dehydrated methanol through the column, to obtain 67.7780 g of a methanol solution of tributylhexadecylphosphonium hydroxide with a hydroxy conversion rate of 52.9%.
[0084] 57.6370 g of this methanol solution was passed again through a column packed with 20 ml of a strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corporation, which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through to obtain 101.0659 g of a tributylhexadecylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 98.1%.
[0085] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final reduced pressure: 85 mmHg) to give a 25.7% methanol solution (tributylhexadecylphosphonium hydroxide:methanol=1:40).
[0086] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 17.32 g (0.01 mol) of 25.7% tributylhexadecylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 9.92 g of tributylhexadecylphosphonium salt (complex 5) as a yellow liquid. 2.50 g of isopropanol was further added, and the mixture was heated and dissolved in a 60°C water bath, obtaining 12.08 g of a yellow liquid.
[0087] <Production Example 6: Butyltriphenylphosphonium salt (complex 6)> Butyltriphenylphosphonium bromide (7.9867 g, 0.02 mol) was dissolved in dehydrated methanol (20 ml) and passed through a column packed with strong basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol). Then, about 35 ml of dehydrated methanol was passed through the column, and 65.5451 g of a butyltriphenylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 50.5% was obtained.
[0088] 55.3890 g of this methanol solution was passed again through a column packed with 20 ml of strongly basic ion exchange resin (Amberlite IRA900(OH)-HG; manufactured by Organo Corp., which had been previously substituted with dehydrated methanol), and then 35 ml or more of dehydrated methanol was passed through to obtain 98.8179 g of a butyltriphenylphosphonium hydroxide methanol solution with a hydroxyl conversion rate of 97.9%.
[0089] The resulting methanol solution was concentrated under reduced pressure at 25° C. (final vacuum degree: 85 mmHg) to give a 20.8% methanol solution (butyltriphenylphosphonium hydroxide:methanol=1:40).
[0090] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 16.17 g (0.01 mol) of 20.8% butyltriphenylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 18 mmHg) to remove isopropanol and methanol, obtaining 8.40 g of a pale yellow solid butyltriphenylphosphonium salt (complex 6). 2.10 g of isopropanol was further added, and the mixture was heated in a 60°C water bath to dissolve, obtaining 10.35 g of a yellow liquid.
[0091] <Production Example 7: Tributyldodecylphosphonium salt (complex 7)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 99.9% was obtained by carrying out the same procedure as in Production Example 4. The resulting methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 17.0% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:60).
[0092] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 22.88 g (0.01 mol) of 17.0% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 12 mmHg) to remove isopropanol and methanol, obtaining 8.72 g of tributyldodecylphosphonium salt (complex 7) as a yellow liquid. 1.00 g of isopropanol was further added to 4.00 g of the mixture, and the mixture was heated in a 60°C water bath to dissolve, obtaining 4.70 g of a yellow liquid.
[0093] <Production Example 8: Tributyldodecylphosphonium salt (complex 8)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 99.9% was obtained by carrying out the same procedure as in Production Example 4. The resulting methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 36.4% methanol solution (tributyldodecylphosphonium hydroxide:methanol = 1:20).
[0094] In a 100 mL eggplant flask, 8.52 g (0.03 mol) of tetraisopropoxytitanium and 10.68 g (0.01 mol) of 36.4% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after nitrogen replacement, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 9.99 g of tributyldodecylphosphonium salt (complex 8) as a yellow liquid. 1.25 g of isopropanol was added to 5.00 g of the mixture, and the mixture was heated in a 60°C water bath to dissolve, obtaining 6.13 g of a yellow liquid.
[0095] <Production Example 9: Tributyldodecylphosphonium Salt (Complex 9)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 97.5% was obtained by carrying out the same procedure as in Production Example 4. The resulting methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 16.9% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:60).
[0096] In a 100 mL eggplant flask, 7.10 g (0.025 mol) of tetraisopropoxytitanium and 11.47 g (0.005 mol) of 16.9% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after replacing with nitrogen, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to distill off isopropanol and methanol, obtaining 6.22 g of tributyldodecylphosphonium salt (complex 9) as a pale yellow liquid.
[0097] <Production Example 10: Tributyldodecylphosphonium salt (complex 10)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 98.8% was obtained by carrying out the same procedure as in Production Example 4. The obtained methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 16.8% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:60).
[0098] In a 100 mL eggplant flask, 5.68 g (0.020 mol) of tetraisopropoxytitanium and 11.57 g (0.005 mol) of 16.8% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after replacing with nitrogen, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 17 mmHg) to remove isopropanol and methanol, obtaining 5.34 g of tributyldodecylphosphonium salt (complex 10) as a yellow liquid.
[0099] <Production Example 11: Tributyldodecylphosphonium Salt (Complex 11)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 98.8% was obtained by carrying out the same procedure as in Production Example 4. The obtained methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 16.8% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:60).
[0100] In a 100 mL eggplant flask, 5.68 g (0.02 mol) of tetraisopropoxytitanium and 23.13 g (0.01 mol) of 16.8% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after replacing with nitrogen, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 11 mmHg) to remove isopropanol and methanol, obtaining 7.04 g of tributyldodecylphosphonium salt (complex 11) as a yellow liquid.
[0101] <Production Example 12: Tributyldodecylphosphonium salt (complex 12)> A tributyldodecylphosphonium hydroxide methanol solution with a hydroxy conversion rate of 97.5% was obtained by carrying out the same procedure as in Production Example 4. The resulting methanol solution was concentrated under reduced pressure at 25°C (final reduced pressure of 85 mmHg) to give a 16.9% methanol solution (tributyldodecylphosphonium hydroxide:methanol=1:60).
[0102] In a 100 mL eggplant flask, 2.84 g (0.01 mol) of tetraisopropoxytitanium and 22.94 g (0.01 mol) of 16.9% tributyldodecylphosphonium hydroxide methanol solution were charged in this order, and after replacing with nitrogen, the mixture was thoroughly mixed with a stirrer. The mixture was heated in a 60°C water bath and concentrated under reduced pressure (final reduced pressure of 16 mmHg) to remove isopropanol and methanol, obtaining 5.23 g of tributyldodecylphosphonium salt (complex 12) as a yellow liquid.
[0103] (Preparation of Moisture-Curable Composition) Moisture-curable compositions were prepared by mixing and kneading the components obtained in the above Production Examples and commercially available components in the mixing ratios (parts by mass) shown in Table 1. The operations of mixing the materials, kneading, and curing were carried out in an atmosphere of 25±1°C and 50-60% RH.
[0104] <Measurement of tack-free time> The obtained moisture-curable composition was measured for tack-free time (the time required from the end of kneading until the sample no longer adheres to the fingertip when the surface is lightly touched with a fingertip cleaned with ethyl alcohol). The results of the tack-free time measurement are shown in Table 1.
[0105] As shown in the Examples and Comparative Examples, the activity is significantly improved when the titanium compound [B1] and the organic onium salt, phosphonium hydroxide [B2], are used in combination, compared to when each is used alone.
[0106] [Table 1]
[0107] The details of the materials shown in Table 1 are as follows:
[0108] (Polymer [A]) MS Polymer SAX520: Silyl group-containing organic polymer (manufactured by Kaneka Corporation) MS Polymer S303: Silyl group-containing organic polymer (Kaneka Corporation) STP-E15: Silyl group-containing organic polymer (WACKER Chemical Corporation)
[0109] (Curing catalyst [B]) Complexes 1 to 12: Produced in Production Examples 1 to 12
[0110] (Other catalysts) Titanium tetraisopropoxide: manufactured by Tokyo Chemical Industry Co., Ltd. Tetrabutylphosphonium hydroxide: 17.6% tetrabutylphosphonium hydroxide methanol solution, prepared in Preparation Example 1
[0111] (Filler) Carlex 300: Calcium carbonate (manufactured by Maruo Calcium Co., Ltd.) FR-41: Titanium oxide (manufactured by Furukawa Chemicals Co., Ltd.) REOLOSIL PM-20: Fumed silica (manufactured by Tokuyama Corporation)
[0112] (Other additives) DINP: Plasticizer (JPlus Corporation) PPG1000: Plasticizer (Kishida Chemical Co., Ltd.) Disparlon 6500: Anti-sagging agent (Kusumoto Chemical Co., Ltd.) Songsorb 3260P: UV absorber (manufactured by SONGWON) Sabostab UV70: Light stabilizer (SONGWON) Irganox245: Antioxidant (BASF Japan Ltd.) KBM-1003: Dehydrating agent (Shin-Etsu Silicone Industries Co., Ltd.) KBM-903: Adhesion promoter (Shin-Etsu Silicone Industries Co., Ltd.)
Claims
1. A curing catalyst [B] for use in curing a polymer [A] having a reactive hydrolyzable silicon-containing group, comprising: The curing catalyst [B] contains a complex of a titanium compound [B1] and an organic onium salt [B2], The titanium compound [B1] is represented by chemical formula (1): The organic onium salt [B2] is a curing catalyst [B] represented by chemical formula (2). (R 1 -O) n Ti-A 4-n (1) (In the formula R 1 is a substituted or unsubstituted hydrocarbon group, n is 1 to 4, and A is a β-diketone group. 【Chemistry 2】 (In the formula, R 2 , R 3 , R 4 and R 5 are the same or different and each represents a substituted or unsubstituted hydrocarbon group. X represents a hydroxyl group.)
2. A moisture-curable composition comprising the curing catalyst [B] according to claim 1 and the polymer [A].
3. A method for producing a cured product, comprising a step of contacting the moisture-curable composition described in claim 2 with moisture.
4. A method for producing a curing catalyst [B] used for curing a polymer [A] having a reactive hydrolyzable silicon-containing group, comprising the steps of: a step of reacting the titanium compound [B1] with the organic onium salt [B2] in a mixture containing the titanium compound [B1] and the organic onium salt [B2] to produce a complex of the titanium compound [B1] and the organic onium salt [B2], The titanium compound [B1] is represented by chemical formula (1): The organic onium salt [B2] is represented by chemical formula (2). (R 1 -O) n Ti-A 4-n (1) (In the formula R 1 , a substituted or unsubstituted hydrocarbon group having 1 to 10 carbon atoms, n is 1 to 4, and A is a β-diketone group. 【Chemistry 2】 (In the formula, R 2 , R 3 , R 4 and R 5 are the same or different and each represents a substituted or unsubstituted hydrocarbon group. X represents a hydroxyl group.) 5. The method according to claim 4, The molar ratio of the titanium compound [B1] to the organic onium salt [B2] in the mixture is 0.1 to 100.
Citation Information
Patent Citations
Mandrel for molding plastic spiral corrugated pipe
JP1979046265A
Organopolysiloxane composition curable to elastomer and use
JP1985161457A
Detection of warp yarn feed-out abnormality in loom
JP1988042942A
Curable composition
JP1996041358A
Curable composition and coating material containing the same
JP1999148022A